Duelo y Estilos de Apego en Jóvenes Universitarios que Atraviesan por una Ruptura Amorosa - Rivera Rodríguez, Juan Diego (Universidad Antonio Nariño, 2023)
In the present work, the way in which the style of attachment in young people who go through a sentimental or affective love breakup association the appearance of a mixed symptomatology of anxiety and depression was investigated, basically the first affective bonds were explored, first relationships and how to face them with a hermeneutical historical approach,with a type of qualitative research, in terms of design, this research was based on aphenomenological design through a narrative interview as a data collection instrument in a focus group and in In relation to the synthesis, a matrix of procedures and a matrix of analysis of results.